Hubungan Kecemasan dan Kejadian Pre Eklamsia di RSUD dr. R. Goeteng Tarunadibrata Purbalingga - Alfi Noviyana; Purwati Purwati (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
The conditions of pregnancy can increase anxiety in women, therefore it can cause a negative impact on pregnant women themselves and on their fetuses. Anxiety is one of the risk factors of the incidence of pre-eclampsia in pregnant women. Pre-eclampsia is still the top three causes of maternal death in the field of obstetrics in Indonesia. The purpose of this study is to know and analyze the relationship of anxiety with the incidence of pre-eclampsia in RSUD Dr. R. Goeteng Tarunadibrata Purbalingga. This research is a quantitative study, with case control design, sampling technique with an accidental sampling approach. Data collection using a standard questionnaire from Hamilton. Analysis in quantitative studies using the X2 test (chi square) The results of this study that there is no statistical relationship between anxiety and the incidence of pre-eclampsia with a value of Ï = 0.732 but clinically found that mothers with anxiety have a risk of 1, 26 times higher experience pre-eclampsia ( value of OR = 1.26). As for some external variables in this study that theoretically become a predisposing factor for pre-eclampsia including age, previous history of pre-eclampsia or hypertension, hereditary history, history of hormonal family planning acceptors related to pre-eclampsia.